1984
DOI: 10.1094/pd-69-502
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Citrus Rootstocks toPhytophthora citrophthoraDuring Winter Dormancy

Abstract: grafted on resistant sour orange stocks, show high incidence of infection in the Resistance of 70 citrus genera, species, and cultivars to Phytophthora citrophthora was eastern Mediterranean area. This paper investigated during winter dormancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Kibris, Poncirus trifoliata cvs Yerli, Jacobson, SEAB, Luisi, Rubidoux, Benecke, Rich, Ferme Blanche, citrange cv. Troyer and C. ampullaceae (Tuzcu et al, 1984). Goksedef (1980) found a direct relationship between the quantity of pectic substances in bark tissues and resistance of rootstocks to P. citrophthora, and concluded that the rootstock containing the highest amount of pectic substances was the most resistant.…”
Section: Phytophthora Diseases Of Citrusmentioning
confidence: 99%
“…Kibris, Poncirus trifoliata cvs Yerli, Jacobson, SEAB, Luisi, Rubidoux, Benecke, Rich, Ferme Blanche, citrange cv. Troyer and C. ampullaceae (Tuzcu et al, 1984). Goksedef (1980) found a direct relationship between the quantity of pectic substances in bark tissues and resistance of rootstocks to P. citrophthora, and concluded that the rootstock containing the highest amount of pectic substances was the most resistant.…”
Section: Phytophthora Diseases Of Citrusmentioning
confidence: 99%